EFEKTIVITAS MUATAN DALAM PENGAJARAN MATA KULIAH AKUNTANSI KEUANGAN DAN PENGAUDITAN SEBAGAI SALAH SATU ALTERNATIF DALAM MEWUJUDKAN BERKURANGNYA KASUS EXPECTATION GAP - Sapariyah, Rina Ani (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2013)
This research has correlation with Lesson Financial accounting and Accountancy Inspection/Auditing, and in this research is aimed to know the content of effectiveness instruction of Financial Accounting and Accountancy Inspection/auditing in lessening or eliminate gap expectation that exist in business world. This research use survey method which is in form of questioner, population taken from public accountant which practice as auditor in Surakarta region and S1 of Accountancy STIE-AUB Surakarta student. Responder divided to two comparison, first comparison is between student which has not yet taken Lesson of Auditing with student which have taken Lesson of Auditing, while second comparison is between student which have taken Auditing lesson with Auditor. Variables that researched are performance attribute, communications and responsibility result of audition. data examination is conducted after data tested its kolmogorof smirnov, validity test use the correlation of moment product and reliability test use cronbach alpha Result of normality test show abnormal value with < 0,05 that make the testing data is needed using non parametric statistic test, in this thesis writer choose Mann Whitney U. Validity test show Valid with value> r tables (0,159). Reliability test show Capable with value to the 0,600. Examination of data Statistical using non parametric Mann Whitney from the third variable of first comparison is performance attribute 0,737 > 0,05 (not significant), auditor responsibility 0,446 > 0,05 (not significant), the communication of the auditing result is 0,000 < 0,05 (significant). The second comparison shows 0,001 < 0,05 (significant) for the attribute of performance, 0,738 > 0,05 (not significant) for the Auditor responsibility and for the communication of auditing result 0,000 < 0,05 (significant). From those numbers we can conclude that Auditing lesson is less effective to reduce expectation gap for performance attribute variables and communication of auditing result, meanwhile for whom auditor responsible, expectation gap can be reduced. Keywods: Expectation Gap, Financial Accounting, Auditing